2022
DOI: 10.3390/medicina58121730
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Outcomes of Critically Ill Pregnant/Postpartum Women with COVID-19 Pneumonia in Western Balkans, The Republic of Srpska Report

Abstract: Background and Objectives: Coronavirus disease 2019 (COVID-19) is a novel infectious disease that has spread worldwide. As of 5 March 2020, the COVID-19 pandemic has resulted in approximately 111,767 cases and 6338 deaths in the Republic of Srpska and 375,554 cases and 15,718 deaths in Bosnia and Herzegovina. Our objective in the present study was to determine the characteristics and outcomes of critically ill pregnant/postpartum women with COVID-19 in the Republic of Srpska. Materials and Methods: The retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…After the elimination of studies not relevant to the subject of interest and meeting abstracts, 25 were retrieved for complete analysis. 4,6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Four studies were excluded: three for including duplicate patients published in other included articles [40][41][42] and one because of the inability to determine from published information the number of women with maternal mortality. 43 The corresponding authors for the latter study were contacted and indicated that they could not provide the additional information requested.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…After the elimination of studies not relevant to the subject of interest and meeting abstracts, 25 were retrieved for complete analysis. 4,6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Four studies were excluded: three for including duplicate patients published in other included articles [40][41][42] and one because of the inability to determine from published information the number of women with maternal mortality. 43 The corresponding authors for the latter study were contacted and indicated that they could not provide the additional information requested.…”
Section: Resultsmentioning
confidence: 99%
“…In total, 21 studies with 386 pregnant individuals who had critical COVID-19 managed with ECMO were included in the review. 4,6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] Study characteristics and results were summarized and verified for accuracy independently by two authors. Features of the included studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations